Green precision engineering: Eco-efficient milling cutter parameters for reduced material waste in profile shaft formation - Malneva Yu.A.; Kuts V. V.; Kalchenko A.N.; Tolmacheva T.A. (E3S Web of Conferences)
The article reflects the results of a study of the influence of the design parameters of the enclosing milling cutter with radial structural feed on the error of forming RK-profile shafts. The method of forming RK profile shafts using a covering milling cutter with a constructive feed is described, the equation of the profile of the producing surface of the milling cutter is given. The values are obtained and the dependence is established for the minimum average radius of the profile of the enclosing cutter, which ensures the fulfillment of the shaping conditions. The discrepancy between the angular positions of the milling cutter teeth set by parametric angles and their actual (geometric) angular position is shown. A method is proposed for calculating the value of the parametric angle of the teeth of the enclosing cutter through the values of their actual (required) angular position. A study was performed and a regression equation was established describing the effect on the shaping error of the average radius of the enclosing milling cutter and the number of teeth with their uniform arrangement, the use of this equation made it possible to establish the ranges of permissible values of the design parameters of the designed milling cutters providing the required shaping accuracy.